Hiding in Plain Sight - Ellis, Mary 1951- (London Severn House, 2018)
On the run from a troubled past, Kate Weller, the newest member of Price Investigations, covers her tracks, changes her name and takes a case in Charleston, South Carolina, where she can hide in plain sight. Renting a charming room with a waterfront view, Kate sets about trying to locate her adopted client's natural siblings, only to find more questions than answers when she eventually tracks down a long-lost sister. Meanwhile, her new landlord won't stop sticking his nose into her case. As far as Kate's concerned, Eric Manfredi should focus on whatever competitor is bent on ruining his family business. But when petty vandalism turns lethal, and Eric's father is arrested for murder, Kate is determined to prove his innocence. Can she find the real culprit before a killer from her own past tracks her down?
Keywords: Weller, Kate (Fictitious character) -- Fiction; Private investigators -- Fiction; Private investigators; Detective and mystery fiction; Detective and mystery fiction; Fiction; romantic suspense novels